(untitled) (Scientific journal of the Fergana State University, 2023)
The article focuses on the result of the field research aimed to define the early system of defence in the ancient and medieval settlements. According to the comparative analyses of the excavations, it has been recorded that Kushtepa-2 defense system had existed since the first settlement was established